Premixed combustion and emission characteristics of methane diluted with ammonia under F-class gas turbine relevant operating condition - Zhang, Yanfei; Zhao, Dapeng; Li, Qin; Huang, Mingming; Hao, Qing; Du, Jianji; Song, Yang; Ming, Zhaoqing; Wang, Jihang (Frontiers in Energy Research, 2023)
Ammonia has been used on a small scale in other industrial equipment such as gas turbines as a carbon-free fuel. However, ammonia fuel suffers from disadvantages such as high ignition temperature, low flame velocity and high NOx emissions. Doping with ammonia using a more reactive fuel, such as methane, can solve the above problems. Therefore, under the relevant operating conditions of the gas turbine (T=723 K, p=16.5 atm), the effect of ammonia content on the combustion and emission characteristics of laminar premixed methane flames was numerically investigated. This can provide a reference for our subsequent research on gas turbine operating conditions. This research uses PREMIX code from ANSYS CHEMKIN-PRO and Okafor chemical kinetic mechanisms. Firstly, the emission data of major pollutants under different ammonia content (XNH3= 0-1.0) and equivalent ratio (Φ= 0.6-1.4) were calculated. Then, the laminar premixed flame structure is analyzed under the lean fuel conditions associated with gas turbines (Φ=0.6, 0.8). Finally, the effect of ammonia addition on the chemical reaction path of NO and CO emission was studied. The results show that ammonia/methane mixture fuel is more suitable for combustion at 0.6-0.8 equivalent ratio under high temperature and pressure. High ammonia content (XNH3>0.6) and low equivalent ratio can reduce NO and CO emissions. The molar fractions of H, O and OH radicals and flame temperature decreased with the increase of ammonia content. In addition, high temperature and high pressure conditions and ammonia content have great influence on the reaction path of NO and CO production. The increase in pressure resulted in a change in the main reaction that produced no. In conclusion, this study provides guidance for reducing the emission of NO and CO from lean side of gas turbine plant.